2003
DOI: 10.1021/cm031017u
|View full text |Cite
|
Sign up to set email alerts
|

Crystalchemistry and Oxide Ion Conductivity in the Lanthanum Oxygermanate Apatite Series

Abstract: The La 10-x (GeO 4 ) 6 O 3-1.5x (9.33 e 10 -x e 10) apatite series has been synthesized and single phases have been obtained in a narrow compositional range (9.52 e 10 -x e 9.75). The apatites' phases are hexagonal (space group (s.g.) P6 3 /m) for 9.52 e 10 -x e 9.60 and triclinic (s.g. P1 h) for 9.66e 10 -x e 9.75. The room-temperature crystal structures have been determined from joint Rietveld refinements of neutron and synchrotron X-ray powder diffraction data. La 9.60 (GeO 4 ) 6 O 2.40 is hexagonal (a ) 9.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
81
1
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(91 citation statements)
references
References 37 publications
8
81
1
1
Order By: Relevance
“…No other band is found at higher frequencies, up to at least 1200 cm -1 . According to Hardcastle et al [42], this frequency (830 cm -1 ) is much lower than that expected for the stretching of a W-O bond in an ideal WO 4 tetrahedron, suggesting a higher coordination of tungsten in the form of WO 5 or even WO 6 . These results imply the distribution of the interstitial oxygen between both germanium and tungsten.…”
Section: Resultsmentioning
confidence: 72%
“…No other band is found at higher frequencies, up to at least 1200 cm -1 . According to Hardcastle et al [42], this frequency (830 cm -1 ) is much lower than that expected for the stretching of a W-O bond in an ideal WO 4 tetrahedron, suggesting a higher coordination of tungsten in the form of WO 5 or even WO 6 . These results imply the distribution of the interstitial oxygen between both germanium and tungsten.…”
Section: Resultsmentioning
confidence: 72%
“…In all these systems, the ionic conduction is mediated by oxide ion vacancy defects, introduced by aliovalent doping. More recently there has been growing interest in materials, whose conduction process is mediated by oxide ion interstitials [2], an important example being apatitetype silicates/germanates, Ln 9.33+x (Si/Ge) 6 O 26+3x/2 (Ln = rare earth) (Figure 1). The vast majority of the work has so far focused on the silicate systems, although the germanates show some benefits in terms of higher conductivities at elevated temperatures, lower synthesis/sintering temperatures and higher oxygen interstitial contents achievable.…”
Section: Introductionmentioning
confidence: 99%
“…However, one complexity of these high oxygen excess germanates is a change in symmetry from hexagonal to triclinic as x increases. Thus it has been shown that single phase samples of La 9.33+x Ge 6 O 26+3x/2 with hexagonal symmetry can be prepared for x ≤ 0.42, while samples with x > 0.42 exhibit a triclinic cell [4,6,11,14]. A consequence of the lower symmetry cell is a reduction in the conductivity at temperatures below ≈650°C, attributed to enhanced defect trapping, which is a problem in terms of applications [4].…”
Section: Introductionmentioning
confidence: 99%
“…Research interest in this area has grown following the initial reports by Nakayama et al of high oxide conductivities (>10 -3 Scm -1 at 500°C) in rare earth silicates, Ln 10-x Si 6 O 26+y , with the apatite structure [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. The structure of these materials is shown in figure 1.…”
Section: Introductionmentioning
confidence: 99%